Stigma and mental health awareness among caregivers of patients with bipolar affective disorder - Kumar, Prashant; Jha, Rashi; Sinha, Prawin Kumar (International Journal of Advances in Medicine, 2020)
Background: Stigma and poor mental health literacy in caregivers of patients with bipolar affective disorder lead to loss of social support and occupational and financial burden reduced functioning, poor compliance and poorer quality of life for both the patient and the caregiver. With this study we aim to find out stigma and mental health awareness in caregivers of patients with bipolar affective disorder. Methods: 90 caregivers of patients diagnosed with bipolar affective disorder according to International statistical classification of diseases and related health problems (ICD-10) criteria were included in our study. Affiliate stigma scale on caregivers of people with mental illness and Public perception of mental illness questionnaire were applied on them after informed consent and acquiring socio-demographic details. Result: Analysis of the affective dimension of affiliate stigma scale on caregivers showed significant value for emotional disturbance and pressure due to care of Bipolar Affective Disorder diagnosed patient. Domains and the overall score in patients with mania was significantly more than in the patients with depression. The most significant difference (p<0.001) in the opinion of respondents was found with regards to the questions that the mental illness is caused by heredity, substance abuse, personal weakness or by God’s decree. Conclusions: Stigma towards mental disorders worsens the prognosis and compliance towards treatment, therefore, it needs to be assessed in all patients and their caregivers to improve overall well-being and improve acceptance of the patient and the caregiver in the society.